Detection And Analysis Of Defect In Steel Tube Using Vibration Impact Acoustic Emission Method - Abd Halim, Zakiah; Jamaludin, Nordin; Syarif, Junaidi; Syed Yahya, Syed Yusainee (Praise Worthy Prize, 2014)
Currently the tube inspection technologies are normally invasive and time consuming,and therefore,an effective and non-invasive tube inspection method is required.This paper presents the research works on the development of non-invasive and non-destructive defect detection system and analysis for the ASTM A179 seamless steel tubes. Vibration excitation using impact hammer method is used to generate transient stress waves in steel tubes. Specifically,three steel tubes were used including a good steel tube and two steel tubes with through-hole artificial defect at different locations.An acoustic emission technique is utilised to detect and capture the stress waves propagation in the steel tubes.The variations of the stress waves propagated in the different condition of the steel tubes were successfully characterized and differentiated using three conventional statistical features namely root mean square (r.m.s), crest factor and kurtosis.The acquired experimental results show that the newly proposed Vibration Impact Acoustic Emission (VIAE) method is capable of detecting the presence of defect in the steel tubes.